Design and implementation of the stacked, synchronised and iconographic timeline-structured electronic patient record in a UK NHS Global Digital Exemplar hospital. Issue 1 (23rd December 2019) - Hales, Alan Arthur; Cable, David; Crossley, Eleanor; Findlay, Callum; Rew, David Anthony
Abstract : Background: Conventional electronic screen visualisation formats, which use tabs, dropdown menus, lists and multiple windows, present huge navigation challenges to health professionals. A unifying and intuitive interface for the electronic patient record (EPR) has been an elusive goal for software developers for decades. Methods: Since 2009, by working in an agile way, we have built and implemented a fully operational and dynamic system, the University Hospital Southampton Lifelines (UHSL), within our clinical data estate, in a UK university hospital. UHSL permits the continuously updated display of the EPR on a single desktop computer screen in an intuitive format. During this iterative evolution, we have resolved a number of practical challenges in data display, while maintaining our core aims of end-user optimisation and radical simplification of the interface. Concurrently, we have upcycled a significant volume of clinical e-content, some from as far back as 1991, into UHSL, and at a marginal cost. Outcomes: UHSL went live in 2017 for all authorised staff at the hospital. It displays all e-records for 2.5 million patients and for more than 100 million documents and reports. It significantly reduces the screen time to navigate the individual EPR, and it offers substantial productivity gains in designated clinical services. Conclusions: UHSL has considerable further development potential as a National Health Service EPR interface, for the integration, display and ease of understanding of medical records across primary, secondary and community care.